The language of suffering: A commentary on Veena Das's 'How the Body Speaks' (Medicine Anthropology Theory, 2017)
The recently published book 'Affliction' by Veena Das explores the meaning of normalcy, illness, suffering, and loss in the lives of the marginalized urban poor living in and around India’s capital city of Delhi. The language that evolves in such communities to describe the afflictions of the body forms from an amalgamation of terms derived from medical, spiritual, and faith-based systems, resulting in a unique vocabulary that needs to be understood by the clinical service provider. This think piece is a psychiatrist’s interpretation of an anthropological exploration of the understanding of various illness experiences. The commentary focuses primarily on the introductory chapter of the book, entitled ‘How the Body Speaks’, and discusses the various themes and theorizations offered by Das regarding communication about illness. The book and the chapter complement and broaden the biomedical understanding of what constitutes sickness and cure for the vulnerable and the disadvantaged.